(untitled) - Purwaka, Tommy H. (Phillipines, 1999)
This research explores legal and institutional aspects of fisheries and other marine resources management.
Keywords: Coastal zone management,Marine resources,Coastal ecology; Indonesia,Indonesia,Indonesia